First record of a specialist folivore of Chromolaena odorata (Asteraceae) in Togo, and indices of its range expansion in Nigeria: implications for biological control. Issue 8 (3rd August 2018) - Aigbedion-Atalor, P. O.; Idemudia, I.; Adom, M.; Day, M.
ABSTRACT: Pareuchaetes pseudoinsulata is reported for the first time in Togo and widespread in south-western Nigeria, albeit in low densities and difficult to detect. Country-wide surveys are warranted in both countries, with the intention of renewing efforts in the biological control of Chromolaena odorata in western Africa, where the socio-ecological impact of the weed is significant.